If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -2x = -7x + 13 Reorder the terms: 13 + -2x = 13 + -7x Add '-13' to each side of the equation. 13 + -13 + -2x = 13 + -13 + -7x Combine like terms: 13 + -13 = 0 0 + -2x = 13 + -13 + -7x -2x = 13 + -13 + -7x Combine like terms: 13 + -13 = 0 -2x = 0 + -7x -2x = -7x Solving -2x = -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -2x + 7x = -7x + 7x Combine like terms: -2x + 7x = 5x 5x = -7x + 7x Combine like terms: -7x + 7x = 0 5x = 0 Divide each side by '5'. x = 0 Simplifying x = 0
| 5y+3=6y+4+12y | | 8y^3+26y^2+15y=0 | | 4x*x=-11x+3 | | x=5/3*20 | | 2w^2+22w+60= | | 40+.25=25+.45 | | 18=6(u-2)+4u | | 2/3x=9/10 | | 2m+5=11 | | 4(-3+x)=5x+1/2 | | f(x)=(2x-1)(x^2+3)(2x^2-5) | | 7x+5=13-5x | | 3d-8=-6+b | | -2(3-m)=14 | | f(x)=(2x+5)(x^2-2x-5) | | 3x*x+8=-14x | | 2(x-7)=3(x+3) | | 1/2(3y-2)+1/4(6y+7) | | x(2x-3)=26 | | x=26/25*15/44*8/39 | | -12x-3y=4+7x-7y | | 10x^2-4x-24=0 | | 10m-9m= | | 8x^2-36x-24=0 | | f(x)=x(x+2)(x-2)(3x^2-4) | | -12r+4-2r=-7 | | N-2/3 | | -3-m=-(m+3) | | 40x+40= | | 41=8n-5 | | x^2+10x=15x-2x^2 | | f(x)=x(5x-2)(x^2+1) |